Visual Aspects of Intercultural Technical Communication: A Cognitive Scientific and Semiotic Point of View - Risku, Hanna; Pircher, Richard (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2008)
AbstractThis article presents a cognitive scientific view of the role of verbal and visual aspects in the translation of technical texts. The semiotic differentiation between symbols and icons is discussed from both the cognitive scientific and the translation studies perspectives. The article refers to the definition of text as a unit of communication (and translation) that includes both verbal and visual aspects and thus emphasises the function of the visual dimension in translation. The theoretical discussion is related to professional practices in the modern translation workplace: through its discussion of the results of a recent empirical field study based on participant observation over an extended period of time in a translation agency, the present research seeks to determine the extent to which the visual dimension can be taken into account in technical translation. In particular, the results point to the consequences of the use of translation technologies (translation memories, translation management systems, localisation software, etc.) in the modern translation workplace. The dominance of the verbal aspect induced by the use of some such technologies can make it increasingly difficult for translators to pay attention to the visual elements in translation. This stresses the importance of the inclusion of courses on the critical and professional use of translation technologies within translation studies programmes.